Promoting abstinence, being faithful, and condom use with young Africans : qualitative findings from an intervention trail in rural Tanzania - Plummer, Mary Louisa (Lexington Books, 2012)
This book examines how the "ABC" behaviors - Abstinence, Being faithful, and Condom use - can be promoted more effectively with young rural Africans. It draws on an extraordinarily large qualitative study affiliated with a randomized controlled trial in Tanzania. The book assesses the process and impact of the MEMA kwa Vijana adolescent sexual health intervention; examines the motivations and strategies of youth who practiced low risk behaviors; and provides detailed recommendations for school and community programs.</spa